Internet of things and culture of innovation in Public University students - Hermitaño-Atencio, Bernardo Clímaco; Ortiz-Vergara , Martin William; Buleje-Agüero , Grimaldo Wilfredo; Torres-Calixtro, Juan Manuel; García-Rojas, Vidal Cristian (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The global economic crisis, the problems generated by climate change, the growth of poverty, the decrease in water and food resources, health problems, among others, affect the world population. Since the crises, innovation is one of the areas that has to be promoted from university classrooms. The research was developed within a quantitative approach with pre-experimental design and proposes to determine the influence of the development of Internet of Things (IoT) modules on the innovation culture of students at the National University of Education (UNE). Information was obtained from 62 students of the Telecommunications and Informatics professional career. The results show that the application of the Internet of Things course significantly affects the values, behaviors, climate, resources, processes and results of the culture of innovation.